Let's talk about grief: Protocol of a study on the recognition and psychoeducation of prolonged grief disorder in outpatients with common mental disorders - Groen, Simon P. N.; Menninga, Marijke C.; Cath, Daniëlle C.; Smid, Geert E. (Frontiers in Psychiatry, 2022)
Background: Recognition that the loss of a loved one may result in prolonged grief disorder (PGD) has gained broad attention recently. PGD may disturb daily functioning to such a degree that mental health treatment is required. Because PGD symptoms often resemble symptoms of common mental disorders (CMD) such as anxiety, depressive, and posttraumatic stress disorder, clinicians may not consider a PGD diagnosis. Moreover, cultural varieties in expression of PGD may complicate recognition. This study explores the prevalence of PGD among both natives and refugees with anxiety, depressive, or trauma- and/or stressor-related disorders as well as clinicians’ awareness and knowledge of PGD symptoms. In addition, a psychoeducation module on PGD symptoms is developed through patient expert collaboration. Methods: Prevalence of PGD symptoms is investigated among 50 participants who are referred to outpatient clinics for anxiety, depression, or posttraumatic stress, using the Traumatic Grief Inventory – Self Report Plus (TGI-SR+) and the Bereavement and Grief – Cultural Formulation Interview (BG-CFI). Clinicians will be interviewed on knowledge (gaps) with respect to PGD symptoms. Finally, focus groups with patient experts are held to develop a psychoeducation module tailored to the patients’ needs, norms and values. Results: This study will show prevalence of PGD among patients who are referred for anxiety, depression, and posttraumatic stress, awareness and knowledge of clinicians on PGD symptoms, and will offer patient expert informed psycho-education. Discussion: Research on prevalence and recognition of PGD is vital. Study results of the prevalence of PGD will be compared to previous studies. Recognition of PGD as distinct disorder from CMDs requires clinicians’ awareness of symptoms related to the loss of a loved one. Thereby, clinicians need to take cultural aspects related to death, bereavement and mourning into consideration. Ethics and Dissemination: The study protocol will be carried out in accordance with relevant guidelines and regulations. Exploratory research to assess the prevalence of PGD in patients suffering from CMDs will facilitate adequate diagnosis by increasing clinician’s awareness of PGD symptoms. Tailored PGD psychoeducation, co-created by culturally diverse patient experts and clinicians will be made publicly available.